The role of competency: comparing social intelligence and teaching and learning performance among academics staffs’ in Malaysian private higher education institutions - Kularajasingam, Janitha; Subramaniam, Anusuiya; Kaur, Devinder (Human Resource Management Academic Research Society, 2022)
Academic staff’s social intelligence plays an important part in increasing their teaching and learning performance owing to their magnitude of competency. However, empirical research that associates both constructs is limited. Thus, this research aspires to scrutinise the influence of social intelligence on teaching and learning performance among academic staff with the moderating effect of competency. A self-administered questionnaire survey was used to collect data from 318 academic staff in the business schools of seven Malaysian private higher education institutions located in Klang Valley. SPSS version 26 were used to analyse data. The findings revealed the following: (1) social intelligence has a significant positive influence on competency, (2) competency has a significant positive influence on teaching and learning performance, (3) social intelligence has a significant positive influence on teaching and learning performance and (4) competency significantly moderates the association between social intelligence and teaching and learning performance. Theoretical and practical implications are discussed.